Monetary policy, trends in real interest rates and depressed demand - Paul Beaudry; Césaire Assah Meh (Bank of Canada, 2021)
Over the last few decades, real interest rates have trended downward in many countries. The most common explanation is that this reflects depressed demand due to demographic, technological and other real factors such as income inequality. In this paper we explore the claim that these trends may have been amplified by certain features of monetary policy. We show that when long-run asset demands by households are C-shaped in relation to real interest rates, a feature we motivate through bequest motives, monetary policy has the potential to affect steady-state properties even if money is neutral in the long run. In particular, we show that if monetary policy reacts aggressively to inflation, this supports a steady state where inflation is close to the central bank's target. However, the same aggressive policy simultaneously favours the emergence of, and the convergence to, a second stable and determinate steady state where both the real interest rate and inflation are lower and monetary policy is constrained by the effective lower bound. We discuss how fiscal policy can be used to escape this low-real-rate, low-inflation trap with the potential for a discontinuous response of long-run inflation.
Keywords: E2; E43; E44; E5; E52; E62; E63; H3; H6; H63; 330; Monetary policy; Fiscal policy; Economic models; Inflation and prices; Interest rates; Debt management